Autobiographical narrative and the poetry of the sensitive through the test of cognition (Colloquia Comparativa Litterarum, 2025)
This study challenges the traditional definition of autobiography (cf. Lejeune) and proposes a cognitive approach to the constitution of authors’ autobiographical memory, following the model of Martin Conway et al. S. Freyermuth has chosen to analyse some works by Nan Aurousseau and Jean Rouaud, on the novelistic side, and by Simon-Gabriel Bonnot, on the poetic side, in order to highlight the effectiveness of questioning the traces of autobiographical memory in texts, thus rejecting the necessity of a prior adherence to the autobiographical pact.
Keywords: cognition; autobiographical memory; novel; poetry; Bonnot